Diasporas, Cultures of Mobilities, 'Race' 2 Diaspora, Memory and Intimacy - Barbour, Sarah; Howard, David; Lacroix, Thomas; Misrahi-Barak, Judith (Horizons anglophones, 2015)
Continuing the series on Diasporas, Cultures of Mobilities, 'Race', this second volume extends existing scholarship by exploring a range of multidisciplinary perspectives on the diasporic condition. Embodiment, memory and intimacy form three core themes through which the complexities of diasporic experiences are revealed and transmitted. Closely aligned to these concerns, the impact of de- territorialisation, inherent in the processes of migration and re-settlement, forms a strong thread throughout the collected essays. Authors engage with individual and collective memorial processes embedded in the evolution of diasporic communities, exploring striking comparisons between diverse regions, states, cultures and linguistic zones. The intellectual and critical scope covered by this original collection of new essays is further reflected in the varied geographical origins of the contributors themselves.